2016
DOI: 10.1039/c6ra19469a
|View full text |Cite
|
Sign up to set email alerts
|

Monofunctional platinum(ii) dithiocarbamate complexes: synthesis, characterization and anticancer activity

Abstract: Three heteroleptic platinum(ii) dithiocarbamates with good anticancer potency have been synthesized and characterized. The anticancer activity against five cell lines may be due to their strong complex-DNA adduct formation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Metal dithiocarbamates have been shown to possess promising biological activities [16,17]. Recent studies have shown that metal dithiocarbamates bind DNA in different ways, with varying cytotoxic activities [3,[18][19][20][21][22][23][24][25]. They inhibit NF-kB, which is known to promote tumor cell proliferation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Metal dithiocarbamates have been shown to possess promising biological activities [16,17]. Recent studies have shown that metal dithiocarbamates bind DNA in different ways, with varying cytotoxic activities [3,[18][19][20][21][22][23][24][25]. They inhibit NF-kB, which is known to promote tumor cell proliferation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…An approach to circumvent cross-resistance is to change the functionality on the metal center namely by decreasing the number of available coordination sites. Monofunctional complexes can be active [57,58,59,60] and have the advantage of having ancillary ligands, which, as such, modify sterically and electronically the behavior of the resulting complex.…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacological applications of dithiocarbamate compounds have been popularized scientifically in recent decades. Due to the chemical and structural flexibility of these compounds, their use has been widely investigated as anti-carcinogenic agents [66,67,68,69,70,71,72,73,74,75,76,77], antibacterial [78,79], antiviral [80,81], antifungal [82,83], among others. In this review, we have presented and discussed the different applications of these compounds as potential antiparasitic compounds, more specifically as antitrypanosomatids-drugs against Chagas disease, leishmaniasis, and African trypanosomiasis.…”
Section: Final Considerations and Expectationsmentioning
confidence: 99%